2021
DOI: 10.53378/348730
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Preference on Employability Skills of Business Management and Accounting Graduates

Abstract: Despite a great deal of narrative and anecdotal evidence that communication and interpersonal skills are important for workplace success, little is known about why those skills are important and how possibly to train those skills. This study uses personnel records of a Japanese manufacturing company as well as its training attendance records, and examines the relationship between participation in their interpersonal skills training program and job performance. We compare those who participated in the training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Leadership skills can be identified from six aspects, namely being able to form a vision to focus and challenge the team; able to translate the vision into a clear strategy on what actions to take and what not to; able to recruit, develop and reward team members; focusing on measurable results; able to innovate and learn to sustain a team or organization; and lead yourself [52]. Therefore, leadership skills are very much considered in one of the soft skills that are considered by the industry to accept its workforce [53]. This is in accordance with the results of the questionnaire, it is found that the leadership skills variable has a percentage of 90.67% which is included in the very strong competency criteria or possessed by graduates based on aspects of organizational activity according to the needs of the industry.…”
Section: Resultsmentioning
confidence: 99%
“…Leadership skills can be identified from six aspects, namely being able to form a vision to focus and challenge the team; able to translate the vision into a clear strategy on what actions to take and what not to; able to recruit, develop and reward team members; focusing on measurable results; able to innovate and learn to sustain a team or organization; and lead yourself [52]. Therefore, leadership skills are very much considered in one of the soft skills that are considered by the industry to accept its workforce [53]. This is in accordance with the results of the questionnaire, it is found that the leadership skills variable has a percentage of 90.67% which is included in the very strong competency criteria or possessed by graduates based on aspects of organizational activity according to the needs of the industry.…”
Section: Resultsmentioning
confidence: 99%
“…This can also help the business graduates to improve their personality and can gain individual learning to their career goals. Based on the research findings of Briones et al (2021), technical skills possessed by UNITEN positively related to the employers' level of satisfaction at significant level of correlation result and interpreted as strong in strength. This finding is consistent with the research done in Australia and Kavanagh and Drennan (2008) stated that business graduates with a good technical skill gives higher satisfaction the employers.…”
Section: Technical Skillsmentioning
confidence: 96%
“…In various universities across the country, parameters such as training on leadership, human relations, leadership skills, problem-solving skills, research skills [11], communication skills [12]- [14], technical skills [15], and character [16] are considered adequate as enablers of the high employment rate of graduates. On the other hand, irrelevant skills learned, little work experience [17], determining the root cause of conflicts, and prioritizing problems [18] are considered as needing improvement to further strengthen the employment rate of graduates while lack of professional eligibility are the pulling factors on the unemployment of graduates [19].…”
Section:  Issn: 2252-8822mentioning
confidence: 99%